Influência da adição do metacaulim nas propriedades do concreto em contato com atmosferas agressivas em estruturas de tratamento anaeróbio de esgoto - Cristiano Martins Quintão (2018)
The concrete structures used in anaerobic sewage treatment plants in Brazil are showing a reduction in the useful life in relation to the projected one, due to the deterioration provoked by the biogas produced in these facilities. Such biogas is composed mainly of methane, carbon dioxide and sulfate ions. Faced the need to optimize the durability of concrete used in sewage treatment plants and to use supplementary cementitious materials for the production of more efficient and sustainable concrete, metacaulim was studied in partial replacement with cement. The objective of this research was to evaluate the influence of high reactivity metakaolin on the strength and durability properties of concrete. The research had an experimental and applied character. A reference concrete was dosed and shaped to meet durability requirements in accordance with NBR 6118:2014 and with the consistency of the pumpable slump 120 ± 20 mm. Two other dosages with partial replacement of cement by metakaolin were studied, maintaining the same dosage parameters. A comparison of the properties in the fresh state and in the hardened state were carried out. Mechanical properties and durability evaluation tests were carried out to compare the different concretes in conditions before and after being submitted to biogas, for evaluation and understanding of the changes in concrete properties. The specimens were exposed using metal supports at the inspection and biogas collection points in a reactor at the COPASA Sewage Treatment Plant, in the municipality of Santa Luzia - MG. The results indicated that the incorporation of metakaolin improves mechanical strength and durability properties of the concrete. However, the incorporation of metakaolin to the concrete promoted the increase of the carbonation front, in proportion to the substitution levels in the studied samples. The results allow to conclude that the use of metakaolin in concrete dosage is technically feasible in the production of concrete with higher performance and durability. In order to evaluate the aggressiveness of the concrete exposed to the biogas, a longer period of exposure is necessary to better evaluate the aggressiveness of the environment